INFLUENCE OF SERVICE QUALITY TO CUSTOMER SATISFACTION PT. POS INDONESIA KARAWANG BRANCH - Asep Maulana; Evi Pebriyanti; Evi Depiana; Eriena Eka Wardani; Elfa Alfiani; Dwino Ayenero (Journal of Management and Business, 2019)
PT Pos Indonesia is still less demanded by society so that the number of deliveries by PT POS Indonesia every year Indonesia is unstable. The problem in this research is to know the effect of quality of services on customer satisfaction PT Pos Indonesia. Quality has a close correlation with customer satisfaction to establish a strong relationships with a company. The research methods used in this research is a quantitative method with data collection through questionnaires given to 100 people who have or often use Indonesia Postal delivery service. The questionnaire data becomes the primary data source that is processed using IBM SPSS statistical software 24. Based on the results of data processed through IBM SPSS statistical software 24, it can be seen that the effect of Quality of Service on Customer Satisfaction is 41.5% while 58.5% is influenced by other free variables.